2019
DOI: 10.1002/jcb.29320
|View full text |Cite
|
Sign up to set email alerts
|

A potential prognostic marker and therapeutic target: SPOCK1 promotes the proliferation, metastasis, and apoptosis of pancreatic ductal adenocarcinoma cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC), a common malignancy originated from the digestive system worldwide, has a poor clinical outcome. SPOCK1 is a widely investigated member of the Ca2+‐binding proteoglycan family and functions as an essential driver in several cancers. However, the complex regulatory role of SPOCK1 in PDAC is unclear. Bioinformatics analysis predicted an interrelationship between increased SPOCK1 expression and the clinical characteristics of patients with PDAC. The SPOCK1 expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Studies have indicated that SPOCK1-mediated EMT regulates proliferation and invasion in various malignancies (34). A recent study has shown that SPOCK1 induces EMT to promote PC metastasis and inactivates the PI3K/Akt signaling pathway to attenuate PC cell apoptosis, in vitro and in vivo (35). Our work also showed that the expression level of SPOCK1 was up-regulated and associated with a shorter overall survival in PC.…”
Section: Discussionsupporting
confidence: 69%
“…Studies have indicated that SPOCK1-mediated EMT regulates proliferation and invasion in various malignancies (34). A recent study has shown that SPOCK1 induces EMT to promote PC metastasis and inactivates the PI3K/Akt signaling pathway to attenuate PC cell apoptosis, in vitro and in vivo (35). Our work also showed that the expression level of SPOCK1 was up-regulated and associated with a shorter overall survival in PC.…”
Section: Discussionsupporting
confidence: 69%
“…The expression level of SPOCK1 is associated with overall survival in many cancers, such as urothelial carcinoma, pancreatic ductal adenocarcinoma, prostate cancer, gastric cancer, breast cancer, lung adenocarcinoma and lung squamous carcinoma. 16,24,27,67,73,74 High expression of SPOCK1 is consistent with shorter overall survival time, which indicates that SPOCK1 is associated with poor prognosis in univariate Log rank tests and in the multivariate analysis. There is a link between cancer stage and the expression of SPOCK1.…”
Section: Potential Applications Of Spock1mentioning
confidence: 84%
“…65 SPOCK1-mediated EMT regulates proliferation and invasion via activation of the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway in gallbladder cancer, colorectal cancer, pancreatic ductal adenocarcinoma and glioma. 2,60,66,67 It is worth noting that invasion and metastasis are regulated by SPOCK1 through Slug-mediated EMT in gastric cancer (Figure 2). 16…”
Section: Physiological Functions Of Spock1mentioning
confidence: 99%
“…Zhang et al identified COL8A1 as the prognostic hub gene highly correlated with Wnt2, which is elevated selectively in CAFs, and high coexpression of COL8A1 and Wnt2 was an independent adverse prognostic factor for colon cancer patients (Katoh, 2001;Zhang et al, 2020) proliferation and promoted the apoptosis of GC cells (Zhou et al, 2020). As for SPOCK1, studies have proved SPOCK1 as an EMT-related marker that was closely correlated with tumorigenesis and invasiveness in gastric cancer (Yan et al, 2017;Chen et al, 2018), prostate cancer (Wang et al, 2016), pancreatic cancer (Li et al, 2020), gallbladder cancer (Shu et al, 2015), and lung cancer (Miao et al, 2013). We observed that high-CAF-risk group GC patients were less sensitive to several drugs like lapatinib, and this result fits well with the finding that SPOCK1-regulated EMT derived the acquiring of lapatinib resistance in HER2-positive GC (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%